Nutritional composition and antioxidant properties of spray pitaya powder (Hylocereus polyrhizus [Weber] Briton & Rose) and its supplementation effects on selected biomarkers in normocholestrolemic subjects - Shafie, Siti Raihanah (2012)
Red pitaya is a rich source of dietary fibers, vitamins, minerals and antioxidants. Consumption of fruit products have shown to induce beneficial changes in pathways related to cardiovascular health. Therefore, the present study was designed to determine the nutritional composition and antioxidant properties of spray pitaya powder (SPP) and its supplementation effects on biochemical parameters among normocholesterolemic subjects in Mempaga, Pahang. This study comprises of three phases. In phase one of the study, nutritional composition analysis revealed that SPP contains 10.9% moisture, 1.22 g ash, 1.59 g protein, 80.33 g carbohydrate, 0.007 g fat and 17.70 g total dietary fiber per 100 g SPP. SPP also contained potassium, sodium, magnesium, zinc and calcium. In SPP, the vitamin C content was 17 mg/100 g SPP. Meanwhile, other trace elements are very minute. The data demonstrated that antioxidant properties in SPP using FRAP assay, DPPH and total phenolic exhibited 0.396 mMFeSo4/g (FRAP value), 51.1% (radical scavenging effect) and 156.40 mgGAE/100g (total phenolic content) respectively. This finding showed that SPP contained beneficial nutrients such as dietary fibers, vitamin C, minerals and antioxidants. Phase two of the study (Chapter 4) involved in-vivo experiment to determine the effect of SPP on the liver and kidney function of normal Sprague Dawley rats. A total of 32 Sprague Dawley rats were divided into a control group and three treatment groups, which were given 0.83 g/kg Body weight (BW)/day, 1.67 g/kg BW/day and 2.5 g/kg BW/day of SPP respectively for 4 weeks. During the experiment, body weight and enzyme markers (liver and kidney enzymes level) were measured. Results showed that the body weight of rats significantly increased throughout the study period. There was no significant difference (p > 0.05) in changes of liver enzymes (AST, ALT and ALP) and kidney (BUN and Creatinine) products from both male and female rats in all treatment groups as compared to normal control group throughout the study. On the basis of these results, it demonstrates that daily oral administration of SPP to rats at dose of up 2.5 g/kg BW/day for 4 weeks, which is equivalent to 1500 g fresh red pitaya/60 kg BW/day, was safe as evaluated by the liver and kidney function tests. Data from this study substantiated the use of SPP as a safe food product. Final phase of the study implied a clinical trial which was conducted among normocholesterolemic subjects. A total of 60 subjects from the residents of Felda Mempaga, Bentong, Pahang participated in this study. The study was a single-blinded, cross-over supplementation trial with two weeks of wash out period. The subjects were allocated into 3 different dosages which are 3 (3S), 4 (4S) or 5 (5S) sachets (20 gram each sachet) of SPP to be consumed daily. Repeated Measures ANOVA analysis had shown a significant decrease (p < 0.05) in TC after 4 weeks supplementation of SPP. All three dosages of SPP showed a decreasing trend of TC. The range of TC dropped in SPP group was 20.75% - 30.1% after 4 weeks supplementation. The higher the dosages given to the subjects, the higher the TC level reduced. Similarly, it was noted that SPP supplementation revealed a significant decreased in LDL-C level (p < 0.05). LDL-C decreased by 21.88% (3S), 25.89% (4S) and 27.41% (5S) respectively after 4 weeks of supplementation compared to baseline. Meanwhile, for TG and HDL-C levels, there were only significant difference (p < 0.05) found in the group supplemented with 4 sachets of SPP. The present study also showed an improvement in antioxidant status of the subjects. Both 4S and 5S supplementation groups showed an increased percentage in TAS compared to baseline, although only group 5S performed a significant increased (p < 0.05) by 12.31% after 4 weeks of consumption. Overall, there was no significant differences were noted in all parameters (TC, TG, LDL-C, HDL-C, GLU and TAS) when compared to different dose of supplementation (p > 0.05). This study also found out that the use of this SPP up to the dose of 100g SPP/day showed no adverse effects on liver and kidney functions during 4 weeks supplementation. In conclusion, spray dried pitaya fruit powder gave scientific merits in the area of functional foods for the emerging health food industry in Malaysia. Supplementations of SPP in daily diet would promote the intake of fruit products and the presence of nutritious content in it might have potential benefits to give desired changes in plasma lipid levels and plasma antioxidant status.